2012
DOI: 10.1161/strokeaha.112.662270
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Symptomatic Middle Cerebral Artery Stenosis

Abstract: Another study demonstrated anatomic features related to high complication rate of intracranial angioplasty and stenting, Background and Purpose-To investigate the efficacy and safety of percutaneous transluminal angioplasty and stenting (PTAS) for symptomatic middle cerebral artery stenosis compared with standard medical treatment in a low-risk Chinese population. Methods-A prospective, randomized, controlled, single-center clinical trial was conducted comparing PTAS with medical treatment for symptomatic midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 30 publications
(38 reference statements)
1
54
1
Order By: Relevance
“…Thirty-three trials (97%) were known to be truly randomized (randomization method not reported for one (29)), and 12 (35%) were double blinded ( Table 1). Most (65%) were international trials; of the RCTs restricted to a single country, China led with four (12%) RCTs (16,19,28,33) (Table 1). Main sponsorship (several trials had multiple contributors) was national governments for 19 (56%) RCTs, while eight (24%) were primarily sponsored by the pharmaceutical or device industry (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-three trials (97%) were known to be truly randomized (randomization method not reported for one (29)), and 12 (35%) were double blinded ( Table 1). Most (65%) were international trials; of the RCTs restricted to a single country, China led with four (12%) RCTs (16,19,28,33) (Table 1). Main sponsorship (several trials had multiple contributors) was national governments for 19 (56%) RCTs, while eight (24%) were primarily sponsored by the pharmaceutical or device industry (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…This study not only indicated mechanism of embolization in stroke recurrence, but also showed a new method to confirm patients at high-risk – MES detection. Recently, Miao et al (15) performed a prospective, randomized, controlled, and single-center clinical trial to compare PTAS with medical treatment for symptomatic MCA stenosis (≥70%). The PTAS group received stenting or balloon angioplasty, whereas the medical treatment group received standard medical treatment (aspirin 100 mg plus clopidogrel 75 mg/day), and all the patients were under strict control of the risk factors.…”
Section: The Clinical Outcome Of Intracranial Artery Stenosismentioning
confidence: 99%
“…We also independently reported our prospective registry focused on symptomatic MCA stenosis, which demonstrated a relatively high 1-year complication rate of 19.4%, compared to the medical group of 17.6% ( p  = 0.85) (14). This result was very similar to the later published SAMMPRIS study.…”
Section: Intracranial Stenting For Icad In China Before Sammprismentioning
confidence: 99%